Urgensi Penerapan Cukai Minuman Berpemanis Dalam Kemasan Sebagai Bentuk Perlindungan Kesehatan Konsumen - Pastika, Dinda Bhawika Wimala; Siringoringo, Gracia R. Moselle (Officium Notarium, 2025)
Healthy living is an important part of every individual in the world, with various factors influencing health, one of which is beverage consumption patterns. In Indonesia, especially among the younger generation, consumption of sweetened beverages, especially in consuming Sweetened Packaged Drinks (MBDK), has increased significantly. This phenomenon is triggered by the popularity of drinks that have gone viral on social media and aggressive advertising. The increase in MBDK consumption has the potential to increase various health problems, especially the risk of diabetes among young people. In an effort to control consumption patterns and prevent health risks, the implementation of MBDK Excise is necessary, which is considered to have an impact on several aspects, namely reducing excessive MBDK consumption, the impact on health, socio-economic, and increasing state revenue. The implementation of MBDK Excise has been successfully implemented in various countries, especially in Southeast Asian countries. So far, the implementation of MBDK Excise, which is being implemented by Thailand, Brunei, Malaysia, and the Philippines, has had a positive impact, so the plan to implement MBDK Excise in Indonesia needs to be realized immediately. Therefore, this study aims to analyze the urgency of interpreting MBDK excise duties in implementing regulations. The purpose of this study is to analyze the urgency of implementing the MBDK Excise Tax in implementing regulations as a form of consumer protection. The method used in this research is a normative juridical research method, which involves reviewing secondary literature and then thoroughly analyzing the data for the purposes of this paper.